On allowing for transient variation in end-member δ13C values in partitioning soil C fluxes from net ecosystem respiration - McCloskey, Christopher S.; Otten, Wilfred; Paterson, Eric; Kirk, Guy J. D. (Wiley, 2021)
The use of stable isotope analysis to resolve ecosystem respiration into its plant and soil components rests on how well the end-member isotope signatures (δ13C) are characterised. In general, it is assumed that end-member values are constant over time. However, there are necessarily diurnal and other transient variations in end-members with environmental conditions. We analyse diurnal and seasonal patterns of ecosystem respiration and its δ13C in a C4 grass growing in a C3 soil using fixed and diurnally varying plant and soil δ13C end-members. We measure the end-members independently, and we assess the effects of expected variation in values. We show that variation in end-members within realistic ranges, particularly diurnal changes in the plant end-member, can cause partitioning errors of 40% during periods of high plant growth. The effect depends on how close the end-member is to the measured net respiration δ13C, that is, the proportion of the respiration due to that end-member. We show light-driven variation in plant end-members can cause substantial distortion of partitioned soil organic matter (SOM) flux patterns on a diurnal scale and cause underestimation of daily to annual SOM turnover of approximately 25%. We conclude that, while it is not practicable to independently measure the full temporal variation in end-member values over a growing season, this error may be adjusted for by using a diurnally varying δ13Cplant.
Keywords: C3 and C4 photosynthesis; ecosystem respiration; isotopic flux partitioning; natural abundance; rhizosphere priming effect; soil carbon